Ga-68 pentixafor PET/CT imaging of vascular expression of chemokine receptor 4 (CXCR4) as a marker of arterial inflammation in patients with human immunodeficiency virus infection and its comparison with F-18 FDG PET/CT Imaging - Sathekge, Mike Machaba (University of Pretoria, 2021)
Thesis (PhD)--University of Pretoria, 2020.